We are all completely beside ourselves - Fowler, Karen Joy (G.P. Putnam's Sons, 2013)
Coming of age in middle America, eighteen-year-old Rosemary evaluates how her entire youth was defined by the presence and forced removal of an endearing chimpanzee who was secretly regarded as a family member and who Rosemary loved as a sister.